Is it Better to Stop at C2 or C3/4 in Elective Posterior Cervical Decompression and Fusion?. Issue 7 (1st April 2022) - Roth, Steven G.; Khan, Inamullah; Chotai, Silky; Chanbour, Hani; Stephens, Byron; Abtahi, Amir; Devin, Clinton J.; Zuckerman, Scott L.
Abstract : We compared operative variables, complications, and patient-reported outcomes in patients undergoing elective posterior cervical laminectomy and fusion with an upper instrumented vertebra (UIV) of C2 versus UIV C3/4. The only difference seen was the longer operative time in the C2 group, without any difference between C2 screw type. Abstract : Study Design: Retrospective cohort study. Objective: (a) Compare operative variables, complications, and patient-reported outcomes (PROs) in patients with an upper instrumented vertebrae (UIV) of C2 versus C3/4, and (b) assess outcomes based on C2 screw type. Summary of Background Data: When performing elective posterior cervical laminectomy and fusion (PCLF), spine surgeons must choose the upper instrumented vertebrae (UIV) at the subaxial cervical spine (C3/4) versus C2. Differences in long-term complications and PROs remain unknown. Methods: A single-institution, retrospective cohort study from a prospective registry was conducted. All patients undergoing elective, degenerative PCLF from December 2010 to June 2018 were included. Patients were divided into a UIV of C2 versus C3/4. Groups were 2:1 propensity matched for fusion extending to the thoracic spine. Demographics, operative, perioperative, complications, and 1-year PRO data were collected. Results: One hundred seventeen patients underwent elective PCLF and were successfully propensity matched (39 C2 vs. 78 C3/4). Groups were similar in fusion extending to the thoracic spine ( P  = 0.588). Expectedly, the C2 group had more levels fused (5.63 ± 1.89) compared with the C3/4 group (4.50 ± 0.91) ( P  = 0.001). The C2 group had significantly longer operative time ( P  < 0.001), yet no differences were seen in estimated blood loss (EBL) ( P  = 0.494) or length of stay (LOS) ( P  = 0.424). Both groups significantly improved all PROs at 1-year (EQ-5D; NRS-NP/AP; NDI). Both groups had the same percentage of surgical adverse events at 6.8% ( P  = 1.00). Between C2 screw type, no differences were seen in operative time, EBL, LOS, complications, or PROs. Conclusion: In patients undergoing elective PCLF, those instrumented to C2 had only longer operative times compared with those stopping at C3/4. No differences were seen in EBL, LOS, 1-year PROs, and complications. Type of C2 screw had no impact on outcomes. Besides increased operative time, instrumenting to C2 had no detectable difference on surgical outcomes or adverse event rates. Level of Evidence: 3